TB outcomes and mortality risk factors in adult migrants at the Thailand-Myanmar border - Carroll, A; Vincenti-Delmas, M; Maung, BM; Htun, WPP; Nosten, F; Smith, C; Sonnenberg, P (International Union Against Tuberculosis and Lung Disease, 2020)
BACKGROUND: Cross-border migrants at the Thailand-Myanmar border are an underserved and vulnerable population. We aimed to identify the causes and risk factors for TB mortality at a migrant-friendly TB programme.